EXPLORING UNIVERSITY STUDENTS' AWARENESS AND UNDERSTANDING OF FORENSIC CHEMISTRY AND DNA APPLICATIONS: A QUESTIONNAIRE-BASED STUDY - Waled Abdo Ahmed; Emad Yousif; Hamsa Thamer; Raghda Makia; Khalid Zainulabdeen (Universitas Negeri Surabaya, 2026)
Forensic chemistry is a rapidly growing sub discipline of forensic science that plays an essential role in criminal investigations through the examination and analysis of physical evidence, including drugs, explosives, and toxic compounds. Despite increasing demand for forensic chemists in the job market, awareness and knowledge of forensic chemistry among university students particularly undergraduate students in chemistry and biotechnology remain insufficiently explored. This study employed a validated questionnaire to investigate the level of awareness, knowledge, attitudes, and perceptions of 20 undergraduate students at Al-Nahrain University, Iraq, regarding forensic chemistry, DNA analysis, and biotechnology. The results indicated that the majority of participants demonstrated a satisfactory level of awareness: 80% were aware of forensic science, 82% recognized the connection between DNA analysis and forensic science, 84% understood the relationship between DNA and biotechnology, and 91% appreciated the importance of DNA evidence in crime scene investigations. Additionally, 79% expressed interest in pursuing future studies in forensic science. The findings underscore significant educational implications for forensic chemistry curricula, career development pathways, and the broader enhancement of scientific literacy regarding forensic science among university students.